Exercise research associates of Oregon, Inc.
Exercise Research Associates (ExRA) is a non-profit research and consulting company with the purpose of performing and disseminating the results of scientific research in the fields of health, fitness, sports medicine and other related sport science and health disciplines. Our primary area of focus is the epidemiology of sports injuries. This web site provides access to the results of research performed by ExRA staff, most of which have appeared in peer-reviewed professional publications.